Content and face validity in virtual reality with children: a validation in five steps+1 of a wheelchair basketball game - Imanol Ceberio; Mohammad Al-Rashaida; Maitane García; Juan Francisco Lopez Paz; Monika Salgueiro; Nicole Passi; Humberto Pavel; Imanol Amayra (Frontiers in Virtual Reality, 2025)
ObjectiveThe present study is aimed to elaborate and determinate the content and face validity of a virtual reality program attending the perspective of children. This simulation is designed to promote empathy and understanding towards children with motor disabilities through adapted sport scenes. This study proposed a validation approach with six phases to assess technical and aesthetic aspects.MethodSample: a) Content validity study, 20 children (11–18 years old) were recruited as lay and content experts, who assessed the properties of grade of realism and physical fidelity of wheelchair basketball scenarios. b) Face validity study, 395 children were recruited as lay experts and divided into two groups (7–9 years old and 10–12 years old), or into ten subgroups according to Age × Gender interaction. The face validity sample assessed the psychological fidelity and the presence of wheelchair basketball scenarios. Instruments: Virtual Reality Content Validity Questionnaire, GAMEX questionnaire and Simulator Sickness Questionnaire (SSQ).ResultsThe content validity study showed preference for technical aspects (music, colors and degree of realism). Therefore, modifications in the design were made. In the content validity study, the high agreement level was influenced by previous sport experiences. In the face validity study, the cognitive development of children determined the differences in agreement levels in some virtual properties (absorption and cybersickness). In this sixth step, the ages 7–8 years versus 10–11 years showed significant differences in validity. The study also criticized the face validity cut-offs often used in adult-focused research, emphasizing the need to adapt them for children´s developmental stages.ConclusionThis study proposes a sixth step not traditionally included in content and face validity processes, specially focusing on the child user. The suitability of content and scenes should follow the same principles of standardization as other methodologies, such as psychometric tests, considering age and gender.